Is This Relevant? Physician Perceptions, Clinical Relevance, and Religious Content in Clinical Interactions - Franzen, Aaron B. (2016)
Despite wide support among physicians for practicing patient-centered care, clinical interactions are primarily driven by physicians' perception of relevance. While some will perceive a connection between religion and patient health, this relevance will be less apparent for others. I argue that physician responses when religious/spiritual topics come up during clinical interactions will depend on their own religious/spiritual background. The more central religion is for the physician, the greater his or her perception of religion's impact on health outcomes and his or her inclusion of religion/spirituality within clinical interactions. Using a nationally representative sample of physicians in the United States and mediated path models, I estimate models for five different physician actions to evaluate these relationships. I find that a physician's religious background is strongly associated with whether or not he or she thinks religion impacts health outcomes, which is strongly predictive of inclusion. I also find that not all of the association between inclusion and physicians' religious background is mediated by thinking religion impacts health outcomes. Issues of religion's relevance for medicine are important to the degree that religious beliefs are an important dimension of patients' lives.
Keywords: clinical interactions; path modeling; patient interactions; Physician beliefs; professional values